Reconstruction of Legal Policy on the Use of Social Media as a Means of Independent Control over Abuse of Authority in Law Enforcement by the Republic of Indonesia National Police - Yosua Farin Setiawan; Rahmadya T. Handayanto; Kif Aminanto (Indonesian Journal Publisher, 2026)
This study aims to analyze the dynamics of abuse of authority in law enforcement by the Indonesian National Police in the era of social media, examine the weaknesses in regulations on the use of social media as a means of independent control, and formulate a reconstruction of legal policies for oversight of law enforcement based on digital technology. The study uses a normative juridical method with a statutory and conceptual approach through an analysis of the 1945 Constitution of the Republic of Indonesia, Law Number 2 of 2002 concerning the Indonesian National Police, the Human Rights Law, the Law on Public Information Disclosure, the Law on Information and Electronic Transactions, and various legal doctrines and theories related to digital accountability and cyber policing. The results of the study indicate that social media has developed into an effective digital social control instrument in exposing various forms of abuse of authority by police officers, such as criminalization, wrongful arrest, excessive force, obstruction of justice, and human rights violations. However, the national legal system still experiences regulatory weaknesses, disharmony of norms, limited internal and external oversight, and the lack of adequate legal protection for citizen reporters and digital whistleblowers. Furthermore, the use of social media also gives rise to various problems such as trial by social media, cyber mob justice, hoaxes, and violations of the presumption of innocence, which have the potential to disrupt the due process of law. Therefore, legal policy reconstruction is needed by strengthening cyber accountability policing, establishing a national digital complaint system, strengthening the authority of the National Police Commission (Kompolnas), protecting digital reporters, validating citizen evidence, and developing a technology-based case handling transparency system to realize a transparent, participatory, democratic, and human rights-based law enforcement system in the digital era.